ANALISIS PERAN GURU DALAM MENINGKATKAN KEDISIPLINAN SISWA DI SDN 18 LIMBOTO - Nabila Baguna; Lia Nurhayati; Yusraningsih H. Pongoliu (Journal of Innovative and Creativity, 2025)
This study aims to analyze the role of teachers in improving student discipline at SDN 18 Limboto. The research method used is qualitative research with a descriptive approach. Data collection techniques include observation, interviews, and documentation, while data analysis techniques used are data reduction, data presentation, and data verification. The results of the study indicate that: (1) Teachers have a strategic role in shaping student discipline through various learning strategies and school rules. (2) SDN 18 Limboto has implemented a discipline program based on school rules with a violation point system and rewards. (3) Teachers use habituation and role model methods in improving student discipline. (4) Obstacles faced in improving student discipline include low student awareness, environmental influences, and lack of consistent supervision. (5) To overcome these obstacles, teachers apply motivational strategies, provide examples, and routine evaluations of student behavior. (6) The implementation of good discipline contributes to improving the quality of classroom learning and a more conducive school environment. This study is expected to be a reference for schools in developing strategies to improve student discipline and provide insight for educators in building an orderly and effective learning environment.